ESTIMATION OF GEOSYSTEM STABILITY AS A METHODOLOGICAL APPROACH FOR DETERMINATION OF THE TECHNOGENIC IMPACT ON GROUNDWATER (CASE STUDY OF QUATERNARY AQUIFER ON THE TERRITORY OF RIVNE NPP) - Brovko, A.; Brovko, G.; Koshliakov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The goal of the research is to determine the degree of stability for the Quaternary aquifer against technogenic impacts on the territory of Rivne NPP (Rivne nuclear power plant). When estimating groundwater stability the statistical methods and methods of mathematical and cartographic modeling were applied. Hydrodynamic, hydrogeochemical and hydrogeothermal components of groundwater system in time were characterized. The degree of groundwater stability to anthropogenic impact was estimated on the Rivne NPP industrial site. It was established that this impact revealed itself in chemical and hydrothermal changes. We observed increase in mineralization and temperature of groundwater. For today this effect is of local character with a tendency to capture more and more territory in the course of time. Reliability of the results of this research is confirmed by using two methodological approaches, namely, statistical and mathematical cartography. The groundwater condition is defined to be weakly broken in accordance with the general environmental state, and the ecological status of the zone is determined as a risk zone.
Keywords: groundwater system; system's stability; technogenic impact; GIS